Ethical Issues in Research Involving Participants With Opioid Use Disorder - Anderson, Emily; McNair, Lindsay (Therapeutic innovation & regulatory science, 2018)
In the current epidemic of opioid use disorders, there is both a scientific and ethical imperative to develop effective medical and behavioral treatments for opioid addiction. Research in subject populations with active and ongoing drug addictions bring unique ethical considerations and challenges. Sponsors, researchers, and institutional review board (IRB) members should be familiar with these unique ethical and medical issues as they design, review, and conduct research planned for this population. Issues include those of informed consent and decision-making capacity of research participants, compensation for participation and concerns about undue inducement, forces that threaten the voluntary nature of research participation including the scarcity of available drug treatment programs, and ensuring that participants are aware of and understand risks that may continue after research participation such as increased risk of overdose after research-mandated drug abstinence. This manuscript discusses the current thinking on these issues.